Recent Advances in Twisted‐Fiber Artificial Muscles. (18th December 2020) - Leng, Xueqi; Hu, Xiaoyu; Zhao, Wubin; An, Baigang; Zhou, Xiang; Liu, Zunfeng
Abstract : An artificial muscle is a type of actuator that can contract, extend, or rotate when exposed to external stimuli (e.g., electrochemical, temperature, pressure, humidity, light, etc.). Twisted fibers can be used in powerful artificial muscles and can convert volume expansion upon stimuli into torsional rotation or axial contraction due to their spiral structure. Upon twist insertion, torsional stress is produced in the fiber, and fiber volume expansion increases the torsional stress, resulting in fiber untwisting. By inserting twist to form a self‐coiled fiber, fiber volume expansion causes the contraction of this self‐coiled fiber if the fiber is torsionally tethered. Fiber‐based artificial muscles have potential applications in a variety of fields such as temperature‐regulating clothing, soft robots, prosthetics, and exoskeletons. Herein, the recent progress in twisted‐fiber artificial muscles with different actuation stimuli, such as thermal, photo, solvent adsorption or infiltration, and electrochemical, is reviewed. The opportunities and challenges for twisted‐fiber artificial muscles are also discussed. Therefore, this review provides an insight for designing high‐performance and multi‐functional twisted‐fiber artificial muscles and motivates the development and applications of fiber‐based artificial muscle in future research. Abstract : This review summarizes the recent advances of fabrication, properties, and applications of twisted‐fiber artificial muscles, including actuation mechanisms, different stimuli (thermal‐, electrochemical‐, photo‐actuation, and solvent adsorption or permeation), and actuation properties. It provides an insight for designing the high‐performance and multi‐functional twisted‐fiber artificial muscles, and motivate the development and applications of fiber artificial muscle in future research.